Epidemic disease risks and implications for veterinary services - Jost, C.C.; Machalaba, C.; Karesh, W.B.; McDermott, John J.; Beltrán Alcrudo, D.; Bett, Bernard K.; Tago, D.; Wongsathapornchai, K.; Plee, L.; Dhingra, M.S.; Pfeiffer, Dirk U. (World Organisation for Animal Health, 2021)
Growth in the livestock sector is associated with heightened risk for epidemic diseases. The increasing spillover of new diseases from wildlife is being driven by wide-scale anthropogenic changes allowing for more frequent and closer wildlife-human and wildlife-livestock contacts. Increasing epidemics in livestock are associated with rapid transition of livestock systems from extensive to intensive, and local to global movement of livestock and their products through value chain networks with weak biosecurity. Major livestock epidemics in the past two decades have had substantial economic impacts, and the COVID-19 pandemic highlights the devastating socio-economic consequences that spillovers can have when not identified and controlled early in the process of emergence. This highlights the importance of Veterinary Services to integrated, whole-of-society efforts to control infectious diseases in animals. Emphasis within Veterinary Services must be placed on prevention and preparedness. We suggest four areas for continued improvement in Veterinary Services to meet this challenge. These include continued development of staff capacity for risk assessment and value chain analysis linked to improved policies and communication, appropriate adaptation of approaches to prevention and control in resource-poor settings, improved multi-sectoral and transboundary cooperation allowing for shared resources and expertise, and systematic approaches that enable Veterinary Services to influence decision-making for trade, markets, business, public health, and livelihoods development at the national and regional levels.